2021
DOI: 10.1177/00031348211060445
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metformin Use on Survival in Patients Undergoing Liver Resection for Colorectal Cancer Metastases

Abstract: Introduction Resection of colorectal liver metastases provides the best chance for survival in patients with Stage IV colorectal cancer; however, hepatic recurrence is frequent and the main cause of death. Multiple epidemiological studies have documented an association between metformin and anti-neoplastic effects in a variety of cancers. Given the vast literature, we evaluated the incidence on recurrence and survival of patients on metformin who undergo surgery for colorectal liver metastasis (CRLM). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…All data utilized for the meta-analysis can be located in Tables 1 and 2. A total of 19 studies (Garrett et al ., 2012; Lee et al , 2012; Cossor et al ., 2013; Spillane et al , 2013; Zanders et al , 2015; Mc Menamin Ú et al , 2016; Paulus et al , 2016; Zhu et al ., 2017; Al Omari et al ., 2018; Baglia et al ., 2019; Dulskas et al , 2019; Mafiana et al , 2019; Vernieri et al ., 2019; Huang et al ., 2020; Kaltenmeier et al ., 2021; Erkinantti et al ., 2022; Scarton et al ., 2022; Seo et al ., 2022; Tarhini et al , 2022) were identified, encompassing 41 832 participants, that assessed the correlation between metformin usage and prognostic-related outcomes. The study included 18 studies (Ng et al ., 2011; Lakha et al ., 2012; Nielsen et al , 2012; Cardwell et al , 2014; Krens et al ., 2014; Hoffmeister et al ., 2015; Shao et al ., 2015; Gray et al , 2016, 2017; Haukka et al , 2017; Lash et al ., 2017; Voorneveld et al ., 2017; Yokomichi et al ., 2017; Mafiana et al , 2019; Erkinantti et al ., 2022; Kim et al , 2022; Pourlotfi et al ., 2022) (including 382 441 participants) evaluating the association between statin use and prognostic-related outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…All data utilized for the meta-analysis can be located in Tables 1 and 2. A total of 19 studies (Garrett et al ., 2012; Lee et al , 2012; Cossor et al ., 2013; Spillane et al , 2013; Zanders et al , 2015; Mc Menamin Ú et al , 2016; Paulus et al , 2016; Zhu et al ., 2017; Al Omari et al ., 2018; Baglia et al ., 2019; Dulskas et al , 2019; Mafiana et al , 2019; Vernieri et al ., 2019; Huang et al ., 2020; Kaltenmeier et al ., 2021; Erkinantti et al ., 2022; Scarton et al ., 2022; Seo et al ., 2022; Tarhini et al , 2022) were identified, encompassing 41 832 participants, that assessed the correlation between metformin usage and prognostic-related outcomes. The study included 18 studies (Ng et al ., 2011; Lakha et al ., 2012; Nielsen et al , 2012; Cardwell et al , 2014; Krens et al ., 2014; Hoffmeister et al ., 2015; Shao et al ., 2015; Gray et al , 2016, 2017; Haukka et al , 2017; Lash et al ., 2017; Voorneveld et al ., 2017; Yokomichi et al ., 2017; Mafiana et al , 2019; Erkinantti et al ., 2022; Kim et al , 2022; Pourlotfi et al ., 2022) (including 382 441 participants) evaluating the association between statin use and prognostic-related outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The patients on metformin showed longer OS in comparison to the non-metformin user group (72 months vs. 60 months, respectively) with an HR of 0.44. Also, a longer recurrence-free survival was reported in the metformin group (HR 0.44) at 49 months vs.33 months in the non-metformin users' group [23]. In addition, a retrospective study by Chu et al, conducted on 6222 type II diabetic CRC patients who underwent surgery from 2000 to 2012, assessed the effect of metformin on OS and liver metastasis risk.…”
Section: Discussionmentioning
confidence: 99%